Nutrition and recovery of women in speed-strength and combat sports (foreign literature review) - Aranson, M. V.; Ozolin, E. S.; Shustin, B. N. (Theory and Practice of Physical Culture, 2017)
Abstract: Studies carried out in recent years showed that information on trends in Olympic sports training technologies is in demand with sports professionals of various levels. However, the supply of information about most important trends of scientific research in elite sport to experts is still limited. The analysis of contemporary literature on training female athletes enabled us to identify priority areas of the current research in this field abroad. The use of extratraining factors, in particular diet optimization and recovery means, is such an area. The article presents research data of foreign experts on the subject.